War and Peace in Mozambique - Chan, Stephen. author. aut Link
XVII, 207 p.
Keywords: The book traces the end of hostilities and the often acrimonious, sometimes naive, but always laboured negotiations towards peace and elections in Mozambique. There is careful examination of the many international factors involved from the covert intervention of South Africa, the reaction of one African state, the role of the United Nations and that of humanitarian and religious groups. The lessons for conflict resolution and peacekeeping for Africa and beyond are discussed.